Modelling landslide using GIS and RS: a case study of upper stream of Langat river basin, Malaysia - Wan Mohd Muhiyuddin Wan Ibrahim,; Ruslan Rainis, (Environmental Management Society, Malaysia, 2004)
Increasing pressure for development in Malaysia in recent years due to rapid population growth and urbanization has caused numerous environmental related problems such as landslide and soil erosion. Increasing landslide event in Malaysia has caused degradation to properties, life and environment. This paper describes a study to develop landslide model by using logistic regression approach, partly to measure the significance of each causative factor that contributes to landslide. In this study causative factors are divided into physical, human activities and location. This model is based upon the model developed by a number of researchers. Landslide events in the Hulu Sungai Langat sub-basin, which is the upper stream of Langat Basin, Selangor, Malaysia were used to develop the model